Implikasi Pejabat Publik Berkampanye dalam Kontestasi Pemilu Presiden dan Wakil Presiden - Sani, Rafif; Mufti, M. Wildan; Sbastyan, Gathan; Purnama, Rendika; Fawwaz, Razky; Yuli, Yuliana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The participation of public officials in the general election campaign for President and Vice President in Indonesia has significant implications for democracy, in particular the potential for misuse of public resources, conflicts of interest, and negative impacts on public services. The use of state facilities for campaigns creates injustice in political competition and damages public trust. To overcome this problem, this study proposes strict regulations that prohibit the use of state resources for campaigns, limit officials' campaign activities, and implement strict law enforcement. Transparency and accountability must also be increased through independent monitoring and civil society participation. These steps are in line with the goal of SDGs 16 to build effective, accountable and inclusive institutions, supporting sustainable development and social justice. This research aims to explore the impact of officials' participation in campaigns and find solutions to maintain democratic integrity and ensure fair political competition.